Análise multidisciplinar da insolvência empresarial das agroindústrias canavieiras no Paraná - Cunha, Athena Mascarenhas da (2023)
Currently, many sugar-ethanol companies or economic groups are facing insolvency or bankruptcy. Sugar-ethanol complexes in the state of Paraná are included in such context, finding themselves in judicial proceedings of company restructure – or already declaring bankruptcy – with the Judicial Power when this study took place. Thus, the main goal of this study is to analyze such procedures of insolvency, considering the financial situation declared to Judicial Power and other possible variables claimed by the broke/recovering companies. That is so mainly because they should be analyzed, in their majority, as members of an economic group that performs many activities of diverse nature and it is that entire conglomerate which requests the benefit as provided by law. For the present study, we used a qualitative and applied methodology with case studies found in previous exploratory and documental research. We included digitalized records of recovery proceedings (RJ) which were active and/or declared bankrupt, publicly accessed on the official websites of the Court of Justice of the State of Paraná (TJPR) and the State of São Paulo (TJSP), also known as Projudi and E-saj, and previous studies on company insolvency, the crisis in the sugarcane and ethanol field and on national development. As outcome, the arguments presented by the companies/groups to prove their delicate economic situation confirm the conclusion found in the literature when it comes to the factors that contribute to the insolvency of sugar-ethanol agroindustry. However, the degree of relevance between the variables was the distinctive factor of this study, as it is possible to affirm that the exogenous variable of the credit crisis post 2008 (and its consequences) can be considered as the main propagator of the financial crisis of businesses. It demanded policies of corporate governance with qualified management to be overcome (which did not happen given administrative features of the companies) and resulted in insolvency.